A label‐free differential proteomics analysis reveals the effect of melatonin on promoting fruit ripening and anthocyanin accumulation upon postharvest in tomato. Issue 2 (11th July 2016) - Sun, Qianqian; Zhang, Na; Wang, Jinfang; Cao, Yunyun; Li, Xingsheng; Zhang, Haijun; Zhang, Lei; Tan, Dun‐Xian; Guo, Yang‐Dong
Abstract: To better understand the function of melatonin in tomato fruit ripening and quality improvement, a label‐free quantitation method was used to investigate the proteins that differ between the control (CK) and 50 μ m melatonin treatment (M50) fruits. Proteomics data identified 241 proteins that were significantly influenced by melatonin. These proteins were involved in several ripening‐related pathways, including cell wall metabolism, oxidative phosphorylation, carbohydrate, and fatty acid metabolism. Moreover, the application of exogenous melatonin increased eight proteins that are related to anthocyanin accumulation during fruit ripening. Additionally, the affected protein levels correlated with the corresponding gene transcript levels. Further, the total anthocyanin content from M50 increased by 52%, 48%, and 50% at 5, 8, and 13 DAT (day after melatonin treatment), respectively. The melatonin‐mediated promotion of fruit ripening and quality might be due to the altered proteins involved in processes associated with ripening. In this work, we indicated that a senescence‐related protein was downregulated in the M50 fruit, while a cell apoptosis inhibitor (API5) protein was upregulated. In addition, peroxidases (POD9, POD12, peroxidase p7‐like) and catalase (CAT3) significantly increased in the M50 fruits. Based on the previous studies and our data, we inferred that melatonin might be positively related to fruit ripening but negatively related to fruit senescence. This research provides insights into the physiological and molecular mechanisms underlying melatonin‐mediated fruit ripening as well as the anthocyanin formation process in tomato fruit at the protein concentration level, and we reveal possible candidates for regulation of anthocyanin formation during fruit ripening.